2019
DOI: 10.1038/s41433-019-0353-y
|View full text |Cite
|
Sign up to set email alerts
|

Acquired onset of third, fourth, and sixth cranial nerve palsies in children and adolescents

Abstract: Purpose To describe the causes of third, fourth, and sixth cranial nerve palsies in children and adolescents. Methods In this retrospective case series, a total of 66 patients aged 0-19 years with third, fourth, and sixth cranial nerve palsies seen in strabismus and neuro-ophthalmic practice from 2010 to 2017 were included. Causes of palsies were determined based on clinical assessment, high-resolution magnetic resonance imaging (MRI), and laboratory work-up. Results Thirty-five patients had sixth cranial nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 25 publications
3
21
0
Order By: Relevance
“…who noticed that 14.5% of their pediatric sixth nerve palsies were of congenital origin[ 3 ], and Park et al . who did not find any congenital case,[ 14 ] 21.7% of the cases in the present cohort were of congenital origin. Rare causes of pediatric sixth nerve palsies reported in the literature include ophthalmoplegic migraine,[ 24 ] Gradenigo syndrome,[ 25 26 ] iatrogenic causes including a lumbar puncture and myelography.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…who noticed that 14.5% of their pediatric sixth nerve palsies were of congenital origin[ 3 ], and Park et al . who did not find any congenital case,[ 14 ] 21.7% of the cases in the present cohort were of congenital origin. Rare causes of pediatric sixth nerve palsies reported in the literature include ophthalmoplegic migraine,[ 24 ] Gradenigo syndrome,[ 25 26 ] iatrogenic causes including a lumbar puncture and myelography.…”
Section: Discussionmentioning
confidence: 52%
“…[ 1 ] Various other authors have found neoplasms to be the most common etiology. [ 14 22 23 ] Trauma was the most common cause for pediatric sixth nerve palsy in the present cohort. In contrast to Harley et al .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The abducens nerve is the most commonly affected cranial nerve in acute strabismus in children 27 . The most common etiology is tumor, reported in up to 45% of the children 28,29 …”
Section: Mri Of the Orbitsmentioning
confidence: 99%
“…Extraocular muscle weakness is not commonly reported in MS. Sixth nerve palsy is a rare presentation of adult MS. 14–16 Children reported with sixth nerve palsy is mostly due to neoplasms or trauma. 17 …”
Section: Introductionmentioning
confidence: 99%